2x + 1 = -5 so 2x = -6 so that x = -3 Then 3x - 4 = 3*(-3) -4 = -9 - 4 = -13
2x+3=7 Subtract three from both sides 2x=4 Divide both sides by 2 x=2
The ordered pair is (1, 3).
2x + x + 4 +2x = x + 20 5x + 4 = x + 20 5x - x = 20 - 4 4x = 16 x = 4
y = x + 2 y = -x + 4 x + 2 = -x + 4 2x + 2 = 4 2x = 2 x = 1 y = x + 2 y = 1 + 2 y = 3 (1, 3)
Do you need this equation factored or? 2x+3=x+4?
3x+4 = 2x-3 3x-2x = -3-4 x = -7
4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4
x over 4= 2x+3 over 15
2x-4
4
2x+3 = 7 2x = 7-3 2x = 4 x = 2
x=4
answer is y=(4/3)-(2x/3)
(3, 1)
(4, -1)
2x + 4 = 10 2x = 10 - 4 = 6 2x = 6 x = 6/2 = 3